2017
DOI: 10.1371/journal.pone.0185376
|View full text |Cite
|
Sign up to set email alerts
|

Cellular heterogeneity contributes to subtype-specific expression of ZEB1 in human glioblastoma

Abstract: The transcription factor ZEB1 has gained attention in tumor biology of epithelial cancers because of its function in epithelial-mesenchymal transition, DNA repair, stem cell biology and tumor-induced immunosuppression, but its role in gliomas with respect to invasion and prognostic value is controversial. We characterized ZEB1 expression at single cell level in 266 primary brain tumors and present a comprehensive dataset of high grade gliomas with Ki67, p53, IDH1, and EGFR immunohistochemistry, as well as EGFR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“… 19 have extensively studied mathematically the role of cell adhesion heterogeneity specifically on cell dissemination, opening the question of whether this heterogeneity is present in gliomas and how it affects the migration mechanisms and tumour morphology. In support to our work, recent studies 14 21 have shown differential expression of cadherins, as well as observable disorganization and instability in cell-to-cell interactions within various GB cell lines. Primary cells most usually overexpress cell adhesion molecules, such as integrins or cadherins, whilst common/established cell lines do not 19 , 43 45 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 19 have extensively studied mathematically the role of cell adhesion heterogeneity specifically on cell dissemination, opening the question of whether this heterogeneity is present in gliomas and how it affects the migration mechanisms and tumour morphology. In support to our work, recent studies 14 21 have shown differential expression of cadherins, as well as observable disorganization and instability in cell-to-cell interactions within various GB cell lines. Primary cells most usually overexpress cell adhesion molecules, such as integrins or cadherins, whilst common/established cell lines do not 19 , 43 45 .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, mechanical feedback through cell-to-cell junctions 13 and/or cell adhesion proteins such as N- and E-cadherin (though the latter is believed to have limited expression in the brain) contribute to the collective migration of glioma cells by promoting direction sensing. Interestingly, differential expression of cadherins has been observed in GB samples, as well as disorganization and instability in cell-to-cell interactions 14 21 , supporting the presence of intratumoural heterogeneity with respect to cell-to-cell adhesion leaving open questions about its role in invasion.…”
Section: Introductionmentioning
confidence: 97%
“…ZEB1 expression has been reported to play a central role in regulating GSCs migration [42]. The expression of ZEB1 did not vary with rigidity in MGAT5 KO GSCs compared to WT GSCs).…”
Section: Discussionmentioning
confidence: 80%
“… 11 In addition, GBM subtypes may significantly differ in their microenvironment, for example, the mesenchymal GBM subtype exhibits a higher immune cell infiltration than all other subtypes. 41 , 54 At present, the only organized multicellular structures where cathepsins K and X have been found to be clustered, are the peri-arterioral regions that function as GSC niches. 22 , 33 , 34 , 35 In these niches, GSCs are surrounded predominantly by endothelial cells, pericytes, smooth muscle cells, fibroblasts and macrophages.…”
Section: Discussionmentioning
confidence: 99%